PENINGKATAN KEMAMPUAN MEMBACA BAHASA ARAB MELALUI TEKNIK PEMBELAJARAN ISTIMA’ PADA SISWA MTs. AL-ANWAR CANGKRINGRANDU PERAK JOMBANG - Bashirotul Hidayah (Muróbbî: Jurnal Ilmu Pendidikan, 2019)
Abstract: Istima has an important role in our lives, because istima is the first means by which humans connect with each other in the stages of their lives. The ability to hear or listen can be achieved by continuous practice to listen to the differences in the sounds of other word elements according to the correct mahroj letters, both directly from the original speaker or through recording. Hearing is meant not only hear by using the ear, but also involves memory and memory. In this case when we hear, our minds are enabled to be able to listen to what we hear in order to get the maximum benefit. A good and capable listener is a listener who is good at choosing and binding on what matters most from what he hears. This listening activity is commonly called listening. So listening is a special skill that can only be achieved through ongoing practice. In general, the purpose of listening exercises is so that students can understand the utterances in Arabic, both everyday and the language used in official forums. The benefit of istima learning techniques is to get the students to hear the utterances and get to know Arabic sound system, besides creating a passionate learning condition by fostering motivation in students so that they can improve their mastery of reading and understand new lessons being taught. That way can improve students' Arabic learning outcomes. There are three focuses examined in this paper, namely the ability to listen to Arabic students, the implementation of listening learning techniques and the constraints of listening learning techniques in Al-Anwar Junior high school Cangkringrandu Perak Jombang. taught. Thus listening is a learning experience that is very important for students and should receive serious attention from the teacher with the aim that students can identify Arabic sounds correctly.